Hedonic Lifestyle as A Moderating Variable of The Influence Of User-Generated Content On Purchasing Decisions - Efti Novita Sari (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study aims to analyze the role of hedonic lifestyle in moderating the influence of User-Generated Content (UGC) on consumer purchasing decisions in the digital era. Amid the rapid rise of social media, user-generated content has become a source of information considered more credible than traditional advertising. However, the effectiveness of UGC in driving transactions often depends on consumers' psychological characteristics and lifestyles, including a hedonic lifestyle. Using a quantitative, survey-based method, this study explores how the interaction between visual content on social media and the tendency to seek personal pleasure affects consumption behavior. The results show that UGC has a significant positive influence on purchasing decisions. Furthermore, a hedonic lifestyle is shown to strengthen this influence, where consumers with high levels of hedonism tend to be more impulsive and responsive to visual stimulation and positive reviews from fellow users. This study provides theoretical contributions to the behavioral accounting and marketing management literature and provides practical implications for marketers in optimizing content strategies based on lifestyle segmentation.